Estonian Information Society (Oxford Cyber Studies) - Nicolaidis, K (University of Oxford, 2015)
Official public domain government documents in Estonia pertaining to cybersecurity and e-government practices, sorted into the following four categories: 1. Legislative Acts 1.1 E-Governance Services 1.2 Information Systems 1.3 Security Measures 1.4 Constitution and Amendments 2. Security Policies and Strategies* 3. Organisational Structures* 4. Incident Data* This qualitative dataset currently comprises Word and PDF documents. * Data will be added in the future. Official public domain government documents in Estonia pertaining to cybersecurity and e-government practices.